Catalytic Kinetic Spectrophotometry Determination of Trace Copper(II) by H2O2 Oxide Acid Fuchsin - Liao, Lixia; Fang, Tao (Asian Journal of Chemistry, 2012)
In this work, kinetic spectrophotometric method for the determination of trace amounts of Cu(II) in the range of 4.0-24 ng mL-1 is reported. The method is based on the catalytic effect of Cu(II) on the oxidation reaction of acid fuchsin by hydrogen peroxide in presence of dilute sulphuric acid (pH = 2.5). The reaction is followed by spectrophotometrically by measuring the change in absorbance (DA) at 546 nm using a fixed time method (6 min). The reaction variables were optimized in order to achieve the highest sensitivity. The 3 s criterion detection limit was 1.36 ng mL-1 and the method was successfully applied to the determination of copper(II) in Songhuariver of Heilongjiang province in China.